Comparative chemical profiling of three TCM drugs in the Paeoniaceae family by UPLC-MS/MS combined with chemometric methods. (April 2019) - Lu, Meng; Hu, Qinmei; Zhang, Yuntian; Zhai, Yanjuan; Zhou, Yuqi; Jiang, Jianqin
Abstract: Paeoniae Radix Rubra (Chi-Shao in Chinese) and Paeoniae Radix Alba (Bai-Shao in Chinese) are two valuable traditional Chinese medicine (TCM) drugs, usually indicated for menstrual disorders and viral infections. Paeonia anomala subsp. anomala (Xinjiang-Shaoyao in Chinese) is taken as Chi-Shao substitute in Xinjiang, China. Due to the diverse growing conditions, there are some differences in chemical compositions of three TCM drugs. An UPLC fingerprint analysis with chemometric methods, including similarity analysis and hierarchical clustering analysis, was applied in the study. By virtue of UPLC-QTOF-MS, 29 components including 18 monoterpene glycosides, 5 galloyl glucoses and 6 phenolic compounds were simultaneously identified. It could be concluded that the UPLC-QTOF-MS combined with chemometric methods could efficiently identify the three TCM drugs, and was a powerful approach for the chemical profiling of three TCM drugs. The developed method provide an available approach for quality control of three TCM drugs. Highlights: UPLC fingerprint combined with chemometric methods was applied to identify three Traditional Chinese Medicine (TCM) drugs. For the first time, an UPLC-QTOF-MS/MS method was developed to compare the chemical profiles of three TCM drugs. 29 compounds were identified through the MS/MS fragmentations. The chemical constituent differences of three TCM drugs contribute to the comprehensive chemical profiling of Paeonia genus.